Developmental changes in nuclear lamina components during germ cell differentiation - Isabella E. Perales; Samuel D. Jones; Katherine M. Piaszynski; Pamela K. Geyer (Nucleus)
The nuclear lamina (NL) changes composition for regulation of nuclear events. We investigated changes that occur in Drosophila oogenesis, revealing switches in NL composition during germ cell differentiation. Germline stem cells (GSCs) express only LamB and predominantly emerin, whereas differentiating nurse cells predominantly express LamC and emerin2. A change in LamC-specific localization also occurs, wherein phosphorylated LamC redistributes to the nuclear interior only in the oocyte, prior to transcriptional reactivation of the meiotic genome. These changes support existing concepts that LamC promotes differentiation, a premise that was tested. Remarkably ectopic LamC production in GSCs did not promote premature differentiation. Increased LamC levels in differentiating germ cells altered internal nuclear structure, increased RNA production, and reduced female fertility due to defects in eggshell formation. These studies suggest differences between Drosophila lamins are regulatory, not functional, and reveal an unexpected robustness to level changes of a major scaffolding component of the NL.